Birefringent crystal and preparation method and application thereof

The synthesis of BaGa(IO3)F4 birefringent crystals by hydrothermal method solved the problems of small birefringent value and unstable physical and chemical properties of existing birefringent crystals, and achieved large birefringent index and stability, which was suitable for the preparation of optical polarization devices.

CN119593064APending Publication Date: 2025-03-11FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411830305.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing birefringent crystals have problems such as small birefringence values ​​and unstable physical and chemical properties in optical communication and optical instrument manufacturing, which limits their use in micro-portable optical communication devices and other applications.

Method used

The hydrothermal method is used to synthesize birefringent crystals with the chemical formula BaGa(IO3)F4. This crystal belongs to a monoclinic crystal system, with a large birefringence, a wide band gap and good thermal stability.

Benefits of technology

It realizes high-performance birefringent crystals with large birefringence index, stable physical and chemical properties and wide transmittance range, which are suitable for the preparation of optical polarization devices and improves the stability and reliability of the devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593064A_ABST
    Figure CN119593064A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of birefringent crystal material preparation, and relates to a birefringent crystal and a preparation method and application thereof. The chemical formula of the crystal is BaGa (IO3) F4, the crystal belongs to a monoclinic system, and the space group is P21 / c; the cell parameters are as follows: a is equal to 10.6-10.7, b is equal to 7.5-7.7, c is equal to 7.6-7.9, alpha is equal to 90 degrees, beta is equal to 109 degrees, and gamma is equal to 90 degrees; the spectrum transmission range of the crystal is 2.5-11 [mu] m, and ultraviolet to middle infrared bands are covered; the birefringence reaches 0.275 (at546 nm) through testing, and the material is a potential excellent birefringence crystal material and can be used for preparing optical polarization devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of birefringent crystal material preparation, and relates to a birefringent crystal and a preparation method and application thereof. Background Art

[0002] Birefringence is an important property in the field of optics. It refers to the phenomenon that when a light beam is incident on an anisotropic crystal, it will be decomposed into two beams of light refracted in different directions. When a light wave is incident on an anisotropic medium, the incident light will be decomposed into two polarized lights with perpendicular vibration directions, different propagation speeds, and different refractive indices. The difference in the propagation paths and speeds of the two beams inside the crystal causes them to have different directions when they emerge from the crystal. This birefringence phenomenon not only enriches the content of optical research, but also provides an important theoretical basis and experimental means for optical communications, polarization information processing and other fields. Crystals that can produce birefringence are called birefringent crystals. They are the core materials for generating and modulating polarized light and are widely used in optical communications, polarization information processing, optical instrument manufacturing and other fields.

[0003] To date, scientists have discovered thousands of crystals with birefringent properties, some of which have been commercialized on a large scale. For example, lithium niobate, yttrium vanadate, calcium carbonate, magnesium fluoride, and α -BaB2O4 and other crystals play an important role in optical communications and optical instrument manufacturing. However, these commercial birefringent crystals have their own shortcomings and limitations. For example, the birefringence values ​​of magnesium fluoride and lithium niobate are relatively small, so they require larger crystal sizes to achieve the desired polarization effect in practical applications, which is not conducive to the development of miniature portable optical communication devices. α Although the comprehensive performance of -BaB2O4 is relatively good, it also has quality problems such as cracking, deliquescence and high-temperature phase change, which limit the practical application of this crystal. Therefore, it is of great significance to develop high-performance birefringent crystals with large birefringence, stable physical and chemical properties and wide transmittance range. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a birefringent crystal and a preparation method and application thereof. The crystal of the present invention has a large birefringence, stable physical and chemical properties and a wide transmittance range.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a birefringent crystal, the crystal chemical formula of which is BaGa(IO3)F4, belonging to the monoclinic system, and the space group is P 21 / c; its unit cell parameters are a=10.6~10.7Å, b=7.5~7.7Å, c=7.6~7.9Å, ɑ =90°,β =109°, γ =90°.

[0006] In a second aspect, the present invention provides a method for preparing a birefringent crystal, which specifically comprises the following steps: A raw material containing barium, a raw material containing gallium, a raw material containing iodine and a raw material containing fluorine are mixed with water to obtain a mixture, which is cooled to room temperature after crystallization, and then filtered, washed and dried to obtain the birefringent crystal.

[0007] Preferably, the molar ratio of barium, gallium, iodine and fluorine in the mixture is (2-10):1:(1-10):2.

[0008] Preferably, the raw material containing barium element is barium carbonate.

[0009] Preferably, the raw material containing gallium element is gallium oxide or single gallium.

[0010] Preferably, the raw material containing iodine element is iodine pentoxide or iodic acid.

[0011] Preferably, the raw material containing fluorine element is hydrofluoric acid or hexafluorophosphoric acid.

[0012] Preferably, the crystallization condition is crystallization at 180°C-260°C for not less than 70 h.

[0013] In a third aspect, the present invention provides an application of a birefringent crystal in the field of preparing optical polarization devices.

[0014] Preferably, the optical polarization device is a polarization prism or a fiber polarizer.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The BaGa(IO3)F4 birefringent crystal of the present invention has a large birefringence index of 0.275 (@546 nm). The crystal has a wide band gap of 4.36 eV, an ultraviolet cutoff edge of 284 nm, and a spectral transmission range of 2.5-11 μ Thermogravimetric analysis shows that the thermal stability of the crystal reaches 450°C, and it is stable in the air without deliquescing and has stable physical and chemical properties.

[0016] Furthermore, the preparation method of the present invention is simple, does not require complicated equipment and cumbersome operating steps, and can obtain a colorless and transparent flaky crystalline material with high purity and high crystallinity by hydrothermal growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 is Ba in the birefringent crystal of the present invention 2+ The coordination environment of the ion; Figure 2 is Ga in the birefringent crystal of the present invention 3+ The coordination environment of the ion; Figure 3 The birefringent crystal of the present invention bc Schematic diagram of the planar layered structure; Figure 4 is the

[010] crystal plane projection of the birefringent crystal of the present invention; Figure 5 Schematic diagram of the band gap value of the birefringent crystal of the present invention; Figure 6 FTIR schematic diagram of the birefringent crystal of the present invention; Figure 7 This is a schematic diagram of the thermogravimetric properties of the birefringent crystal of the present invention; Figure 8 (a) is a schematic diagram of the birefringent crystal of the present invention before extinction; Figure 8 (b) is a schematic diagram of the birefringent crystal of the present invention after extinction; Figure 8 (c) is the measured thickness of the birefringent crystal of the present invention. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings: The first object of the present invention is to provide a birefringent crystal, the crystal chemical formula of which is BaGa(IO3)F4, which belongs to the monoclinic system and has a space group of P 21 / c; its unit cell parameters are a=10.6~10.7Å, b=7.5~7.7Å, c=7.6~7.9Å, ɑ =90°, β =109°, γ =90°. The coordination of metal cations is as follows Figure 1 and Figure 2 As shown, the barium atom forms a 10-coordinate structure with 9 fluorine atoms and one oxygen atom from the iodate, and the gallium atom forms a six-coordinate GaO2F4 octahedron with 4 fluorine atoms and two oxygen atoms from the iodate. Figure 3 As shown, Ba 2+ The large ionic radius of the crystal structure helps to layer the crystal structure. bc The planar layering forms a two-dimensional structure. The layered structure is composed of a Ba-F-Ba-F network as the central skeleton, and the GaO2F4 octahedron and iodate groups are bridged outward in sequence through shared fluorine atoms. a The axial stacking forms a two-dimensional crystal structure, which is beneficial to increase the anisotropy of the crystal, thereby obtaining the high birefringence of BaGa(IO3)F4.

[0025] A second object of the present invention is to provide a method for preparing a birefringent crystal, which specifically comprises the following steps: By adopting a hydrothermal synthesis method, a raw material containing barium, a raw material containing gallium, a raw material containing iodine and a raw material containing fluorine are mixed with water to obtain a mixture, and then the mixture is crystallized at 180°C to 260°C for no less than 70 hours and then cooled to room temperature at a cooling rate of 2°C / h to 8°C / h, and then filtered, washed and dried to obtain the colorless, transparent, flaky birefringent crystal material with high purity and high crystallinity. By controlling the crystallization conditions, the ions or molecules in the raw materials form an ordered crystal structure in the solution.

[0026] The barium element in the birefringent crystal is derived from barium carbonate; the gallium element is derived from gallium oxide or gallium; and the fluorine element is derived from hydrofluoric acid or hexafluorophosphoric acid. The molar ratio of barium, gallium, iodine and fluorine in the mixture is (2-10):1:(1-10):2.

[0027] The third object of the present invention is to provide an application of a birefringent crystal in the field of preparing an optical polarization device, wherein the optical polarization device is a polarization prism or an optical fiber polarizer. The polarization prism and the optical fiber polarizer are important optical elements and are widely used in optical communications, optical information processing, optical measurement and sensing, and other fields.

[0028] The birefringent crystal of the present invention has unique optical properties, and can separate incident light according to different polarization directions, so that the prepared polarization prism or optical fiber polarizer can achieve high-precision polarization separation, effectively filter out unnecessary light polarization components, and thus improve the performance of the optical system. Secondly, the birefringent crystal of the present invention has a stable structure, is not easily affected by the external environment (such as temperature, humidity, etc.), is not easy to break and deliquesce, and the prepared polarization device has excellent stability and reliability, ensuring that the device can maintain stable polarization performance during long-term use, and meets the needs of various optical systems.

[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0030] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0031] Example 1 4 mol barium carbonate, 1 mol gallium oxide, 1 mol iodine pentoxide and 4 mol hydrofluoric acid were mixed with deionized water, crystallized at 260°C for 70 h, cooled to room temperature at a rate of 2°C / h, filtered, washed and dried to obtain the birefringent crystal.

[0032] Example 2 10 mol barium carbonate, 1 mol gallium, 10 mol iodic acid and 2 mol hydrofluoric acid were mixed with deionized water, crystallized at 240°C for 75 h, cooled to room temperature at a rate of 3°C / h, filtered, washed and dried to obtain the birefringent crystal.

[0033] Example 3 12 mol barium carbonate, 1 mol gallium oxide, 2 mol iodine pentoxide and 4 mol hydrofluoric acid were mixed with deionized water, crystallized at 220°C for 80 h, cooled to room temperature at a rate of 4°C / h, filtered, washed and dried to obtain the birefringent crystal.

[0034] Example 4 8 mol of barium carbonate, 1 mol of gallium, 6 mol of iodic acid and 2 mol of hydrofluoric acid were mixed with deionized water, crystallized at 200°C for 85 h, cooled to room temperature at a rate of 6°C / h, and then filtered, washed and dried to obtain the birefringent crystal.

[0035] Example 5 4 mol barium carbonate, 1 mol gallium, 8 mol iodic acid and 2 mol hydrofluoric acid were mixed with deionized water, crystallized at 180°C for 90 h, cooled to room temperature at a rate of 8°C / h, filtered, washed and dried to obtain the birefringent crystal.

[0036] Example 6 10 mol barium carbonate, 1.5 mol gallium, 6 mol iodine pentoxide and 0.5 mol hexafluorophosphoric acid were mixed with deionized water, crystallized at 180 °C for 90 h, cooled to room temperature at a rate of 8 °C / h, filtered, washed and dried to obtain the birefringent crystal.

[0037] Crystal structure analysis of birefringent crystal BaGa(IO3)F4: The structures of the crystals obtained in Examples 1-6 were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0038] Among them, single crystal X-ray diffraction was performed on Agilent's SuperNova Dual Wavelength CCD X-ray single crystal diffractometer. The data collection temperature was 295 K, and the diffraction light source was monochromatic Mo-Kα rays (λ = 0.71073Å); the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-2014 program package; the position of heavy atoms was determined by the direct method, and the coordinates of the remaining atoms were obtained by the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0039] The single crystal X-ray diffraction results show that the birefringent crystals obtained in Examples 1 to 6 have a crystal chemical formula of BaGa(IO3)F4, belong to the monoclinic system, and have a space group of P 21 / c; its unit cell parameters are a=10.6~10.7Å, b=7.5~7.7Å, c=7.6~7.9Å, ɑ =90°, β =109°, γ =90°, its crystal structure is as follows Figure 4 shown.

[0040] Diffuse reflection absorption spectrum and infrared spectrum test: The diffuse reflection absorption spectrum test of the birefringent crystal prepared in Example 1 was carried out on a Lambda-950 UV-visible-near infrared spectrophotometer from Perkin-Elmer, USA. The birefringent crystal sample of the present invention was ground into powder, and BaSO4 was used as a reference substrate. The test results are shown in FIG. Figure 5 As shown, the birefringent crystal band gap is about 4.36 eV and the UV cutoff edge is about 284 nm. The infrared spectrum test was carried out on a Fisher Nicolet S50 FT-IR spectrometer with a wave number range of 4000-400 cm -1 The test results are as follows: Figure 6 As shown, the crystals are between 2.5 and 11 μ m has good transmittance in the spectral range.

[0041] Thermogravimetric testing: Thermogravimetric analysis of the birefringent crystal prepared in Example 1 was performed on a METTLER TGA2. The crystal powder sample of the present invention was heated from 30°C to 900°C at a heating rate of 10°C / min in a nitrogen atmosphere and then kept at this temperature for 10 minutes. Figure 7 Thermogravimetric analysis results show that the thermal stability of the crystal reaches 450 °C.

[0042] Birefringence test: Taking the birefringence of the crystal prepared in Example 1 as an example, it was measured by a Nikon LV100N orthogonal polarization microscope, and the formula is: n×d, where , and represent optical path difference, birefringence and thickness respectively. Figure 8 (a) and Figure 8 (b) shows the polarization phenomenon of the crystal before and after extinction. Figure 8 (c) shows the measured thickness of the crystal is 5.41 μ m. By comparing with the Michel–Lévy diagram, it can be concluded that the optical path difference of BaGa(IO3)F4 is 1.489 μ m, according to the formula, the crystal of the present invention has a large birefringence of 0.275 (@546nm).

[0043] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A birefringent crystal, characterized in that: The crystal chemical formula is BaGa(IO3)F4, belonging to the monoclinic system, and the space group is P 21 / c; its unit cell parameters are a=10.6~10.7Å, b=7.5~7.7Å, c=7.6~7.9Å, ɑ =90°, β =109°, γ =90°.

2. The method for preparing a birefringent crystal according to claim 1, characterized in that: The specific steps include: A raw material containing barium, a raw material containing gallium, a raw material containing iodine and a raw material containing fluorine are mixed with water to obtain a mixture, which is cooled to room temperature after crystallization, and then filtered, washed and dried to obtain the birefringent crystal.

3. The method for preparing a birefringent crystal according to claim 1, characterized in that: The molar ratio of barium element, gallium element, iodine element and fluorine element in the mixture is (2-10):1:(1-10):

2.

4. The method for preparing a birefringent crystal according to claim 2, characterized in that: The raw material containing barium element is barium carbonate.

5. The method for preparing a birefringent crystal according to claim 2, characterized in that: The raw material containing gallium element is gallium oxide or single gallium.

6. The method for preparing a birefringent crystal according to claim 2, characterized in that: The raw material containing iodine element is iodine pentoxide or iodic acid.

7. The method for preparing a birefringent crystal according to claim 2, characterized in that: The raw material containing fluorine element is hydrofluoric acid or hexafluorophosphoric acid.

8. The method for preparing a birefringent crystal according to claim 2, characterized in that: The crystallization condition is crystallization at 180°C-260°C for no less than 70 h.

9. Use of the birefringent crystal according to claim 1 in the field of preparing optical polarization devices.

10. The use according to claim 9, characterized in that: The optical polarization device is a polarization prism or a fiber polarizer.